CORTICOTOMY- ASSISTED ORTHODONTIC TREATMENT - Pisevska, Sofijanka Gerasimova; Simjanovska, Ljuba; Markovska, Mirjana; Petreska, Marija Peeva (Journal of Morphological Sciences; Vol 2 No 2 (2019): JMS, 2019)
Ankylosis of tooth is defined as the fusion of mineralized root surface of the surrounding alveolar bone with the obliteration of the periodontal ligament. Tooth ankylosis can occur at any time during the eruption, and diagnosis can be made by clinical and radiographic evaluation. Conventional orthodontic treatment is insufficient for ankylosis tooth movement and requires special treatment approaches. Corticotomy is a surgical technique which uses osteotomy of the bone for reposition of the ankylosed tooth and adjacent alveolar bone. This paper presents leveling of an impacted and ankylosed upper canine done with corticotomy-assisted treatment. We present a case of  a 12-year-old girl with symmetric face, normal growth development for her age and maintained good oral hygiene and systemic health. The treatment included bimaxillary correction and correction of the dental relationship. Corticotomy-assisted orthodontic treatment was planned for upper right canine tooth, because we assumed that conventional orthodontic treatment might not be successful. Corticotomy-facilitated orthodontics is an effective treatment alternative in adults with severe malocclusion to decrease the treatment time and increase the quality of treatment. The corticotomy cuts and perforation has to be done on cortical bone layer and extend only into the superficial aspect of the medullary bone. Corticotomies can be a powerful and save tool to improve the quality and duration of orthodontic treatment.